Hak Yang Mengering: Kuasa Modal Terhadap Hak Atas Air Di Cikeusal - Syahwal, Syahwal; Gunawan, Muhamad Nabil (Jurnal Hukum & Pembangunan, 2025)
This paper originates from an observation of the water crisis affecting Cikeusal. Recognizing water as an integral part of human rights, we pose the question: why does a water crisis occur in Cikeusal, despite water being recognized as a human right? In addressing this issue, we position water as a resource closely intertwined with political dynamics. Therefore, we employ a socio-legal approach, using autoethnography as the primary method for data collection. Our study reveals that the water crisis in Cikeusal stems from capitalist expansion in the form of extractive industries, specifically karst mining. This capitalist expansion has led to the maldistribution of water resources for Cikeusal residents, ultimately resulting in the water crisis they face today.